Data concurrency is required for estimating urban heat island intensity. (January 2016) - Zhao, Shuqing; Zhou, Decheng; Liu, Shuguang
Abstract: Urban heat island (UHI) can generate profound impacts on socioeconomics, human life, and the environment. Most previous studies have estimated UHI intensity using outdated urban extent maps to define urban and its surrounding areas, and the impacts of urban boundary expansion have never been quantified. Here, we assess the possible biases in UHI intensity estimates induced by outdated urban boundary maps using MODIS Land surface temperature (LST) data from 2009 to 2011 for China's 32 major cities, in combination with the urban boundaries generated from urban extent maps of the years 2000, 2005 and 2010. Our results suggest that it is critical to use concurrent urban extent and LST maps to estimate UHI at the city and national levels. Specific definition of UHI matters for the direction and magnitude of potential biases in estimating UHI intensity using outdated urban extent maps. Highlights: It is essential to map land surface conditions accurately and timely. It is critical to use concurrent urban extent and LST maps to estimate UHI. Definition of urban and surrounding areas matters for the estimate of UHI effect. Abstract : It is critical to use concurrent urban extent and LST maps to estimate UHI, which demands mapping land surface conditions accurately and timely.